THE INCREMENT OF GENETIC POTENTIAL OF MANGOSTEEN THROUGH FERTILIZATION - Enny Adelina; Vanny M A Tiwow; Jeki Jeki; Yohanis Tambing; Nuraeni Nuraeni; Indrawati Noho; Retno Ayu Ningrum; Moh Fahri; Muslim Mahda (Universitas Tadulako, 2023)
Indonesia's mangosteen exports to several Asian countries, Europe, and the Middle East have increased yearly, especially during the Covid19 pandemic. However, efforts to improve domestic mangosteen cultivation technology are inadequate. The research materials used include 45 mangosteen trees accessed by Donggala and Sigi already producing (age + 20 years) and Urea, TSP, and KCL fertilizer. The tools used are meters, plastic labels, calipers, digital scales, Smartphones, and GPS Garmin 64 Sc. Using a RandomIzed Group Design (RAK), one factor, namely fertilization, consists of three levels of treatment in each District. The observation results were analyzed using ANOVA, and if there was a significant influence, it was continued with the BNJ analysis. The results showed that fertilization treatment using BALITBU TROPIKA Solok and analysis results from the Soil Science Laboratory Unit of the Agriculture Faculty University of Tadulako increased plant height and triangular area stamina by 100 to 300 percent compared to without fertilization. There was an increase in plant height and triangular stamina area by 100 to 300 percent compared to without fertilization. There was an increase in plant height and triangular area stamina by 100 to 300 percent compared to without fertilization. There was an increase in production of fruit height from 155 to 394 percent, fruit/seed locul number from 101 to 106 percent, fruit production per tree from 175 to 178 percent, and fruit diameter from 119 to 137 percent.